2021
DOI: 10.3389/fonc.2021.552634
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Machine Learning in Differentiation Between Benign and Malignant Breast Lesions

Abstract: BackgroundDifferential diagnosis between benign and malignant breast lesions is of crucial importance relating to follow-up treatment. Recent development in texture analysis and machine learning may lead to a new solution to this problem.MethodThis current study enrolled a total number of 265 patients (benign breast lesions:malignant breast lesions = 71:194) diagnosed in our hospital and received magnetic resonance imaging between January 2014 and August 2017. Patients were randomly divided into the training g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(42 reference statements)
0
7
1
Order By: Relevance
“…The AUC values of the proposed model in the training and the validation sets were 0.979 and 0.977, respectively, indicating good reliability and diagnostic performance. In addition, the diagnostic performance of the model was better than what was reported in previous research 34–36 . Although the model of this study shows a high sensitivity of 90% and a high specificity of 96%, however, we know that for our research—that is, in a specific diagnostic environment, 10% of our research results have missed diagnosis of cancer, which is a rather high value.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The AUC values of the proposed model in the training and the validation sets were 0.979 and 0.977, respectively, indicating good reliability and diagnostic performance. In addition, the diagnostic performance of the model was better than what was reported in previous research 34–36 . Although the model of this study shows a high sensitivity of 90% and a high specificity of 96%, however, we know that for our research—that is, in a specific diagnostic environment, 10% of our research results have missed diagnosis of cancer, which is a rather high value.…”
Section: Discussioncontrasting
confidence: 72%
“…In addition, the diagnostic performance of the model was better than what was reported in previous research. [34][35][36] Although the model of this study shows a high sensitivity of 90% and a high specificity of 96%, however, we know that for our research-that is, in a specific diagnostic environment, 10% of our research results have missed diagnosis of cancer, which is a rather high value. It will bring many problems to the clinical screening process.…”
Section: Discussionmentioning
confidence: 59%
“…The ML model has been used to differentiate benign and malignant breast nodules in some studies (31)(32)(33). However, few studies used traditional ML methods combined with imaging features to predict NSLN metastasis in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the gradient boosting decision tree (GBDT) algorithm was applied to determine the top-ranked and most valuable features for predicting the tumor response. GBDT was proposed as a tree-based algorithm based on a greedy strategy (called gradient boosting) that evaluates the importance of a texture feature through the time it used as branching point for the tree [19] . After those steps, TR, PTR (3 mm), PTR (5 mm), and PTR (10 mm) radiomics models were separately established using logistic regression algorithm with 5-fold cross-validation.…”
Section: Feature Selection and Radiomics Model Constructionmentioning
confidence: 99%
“…This approach would capture the three-dimensional (3D) information of the entire tumor and has been proved effective in characterizing the heterogeneity of the tumor by acting as a whole tumor virtual biopsy [17,18] . Numerous studies have demonstrated that radiomics-based models effectively identify the diagnosis and pathological characteristics or predict therapeutic e cacy and prognosis of cancer patients for clinical decisionmaking [19][20][21][22] . Recently, there has been increasing interest in evaluating radiomics patterns of the region surrounding the visible tumor [20,23,24] .…”
Section: Introductionmentioning
confidence: 99%